Manifestation of Socio-Cultural Components in the Informal Oral Communication Practices of the Teaching and Non-Teaching Personnel in the Philippines: An Ethnographic Inquiry - Ruby D. Tagocon; Ismael N. Talili (Philippine Association of Institutions for Research, Inc., 2018)
Communication is immensely dynamic in the 21st century as evidenced by the fast-changing communication mechanisms. However, global trends show that oral communication skills are still considered among the most desired skills that employers are seeking in the workplace. Thus, there is a need to explore the manifestation of the socio-cultural components of the personnel, namely: behavior, attitude, and etiquette in their oral communication practices particularly the informal manner, as the components bear a significance when they engage in such form of communication interaction.  Direct observations of thirty-eight episodes of the teaching and non-teaching interactions of the personnel were noted followed by a Focus Group Discussion with seven selected personnel that validated the results of the observed manifestation of their  socio-cultural components and likewise explored other underlying factors that shaped and developed their socio-cultural components. Behavior (facial expressions) and etiquette (voice tone) components mainly dominated in their interactions, yet the attitude component is also significant to them. The manifestation of these components is situational given their respective upbringing during childhood as a major perceived aspect that established these components. A desirable manifestation of these components is encouraged when engaging in informal oral communication interactions so to become a competent communicator in the workplace.